Enhancing the nonlinear thermoelectric response of a correlated quantum dot in the Kondo regime by asymmetrical coupling to the leads - Perez Daroca, Diego Raul; Roura Bas, Pablo Gines; Aligia, Armando Ángel (American Physical Society, 2018)
Fil: Perez Daroca, Diego Raul. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina